SYNTHESIS GLYCEROL STEARATE OF STEARIC ACID WITH GLYCEROL BY PRODUCT OF BIODISEL FROM USED COOKING OIL - Ika Rosdiani; Sri Atun (Jurnal Penelitian Saintek, 2015)
The aim of this research is to synthesis glycerol stearate compound from stearic acid with glycerol by product of biodiesel from used cooking oil, and to determine of product using IR and GC-MS spectroscopy. Method of the research was esterifi cation of glycerol and stearic acid with concentrated HCl as catalyst, by refl uct at 120-160 0C for 8 hours. The result was recrystallized by n hexan. The compound characterized by using IR spectroscopy and GC-MS spectroscopy. The compound has solid form, white to yellowish colour and has 58- 59 0C melting point value with rendement 80.53%. IR spectrum showed the presence C=O carbonil, C-O ester, -OH and C-H aliphatic group. The result of GC-MS analysis showed the compound which have synthesized has similarities with glycerol 2-monostearate with similarity index (SI) of 88% with a purity of 98,94%.